2019
DOI: 10.3390/geosciences9100416
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Physicochemical Properties and Permeability of the Fluvisols and Eutric Cambisols in the Zagreb Aquifer, Croatia

Abstract: The physicochemical properties of soil and the unsaturated zone can have a large influence on the infiltration of precipitation into an aquifer. Soil permeability presents soil property that can be very variable. The main objectives of this study were to estimate differences in soil permeability in two dominant types of soils—Fluvisols and Eutric Cambisols—in the area of the Zagreb aquifer and determine the relationship between the physicochemical properties and the permeability of the analyzed soils. For this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…This transformation may be recognized not only due to a color change, but also as a result of blurring of the micro-stratification of alluvial material, development of a sub-angular instead of angular structure, and subsurface accumulation of organic matter and base cations (as compared to parent material). Similar transformations towards the development of Bw horizons were recognized in most drained alluvial soils [7,10,13,48]. It seems that the formation of Bw horizons may be faster under favorable conditions in the more fertile fine-textured soils (loamy and silty textured), where the well-developed cambic horizons may be recognized over decades after river regulation and soil drainage [30].…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…This transformation may be recognized not only due to a color change, but also as a result of blurring of the micro-stratification of alluvial material, development of a sub-angular instead of angular structure, and subsurface accumulation of organic matter and base cations (as compared to parent material). Similar transformations towards the development of Bw horizons were recognized in most drained alluvial soils [7,10,13,48]. It seems that the formation of Bw horizons may be faster under favorable conditions in the more fertile fine-textured soils (loamy and silty textured), where the well-developed cambic horizons may be recognized over decades after river regulation and soil drainage [30].…”
Section: Discussionmentioning
confidence: 75%
“…Although many authors reported the transformation of drained alluvial soils towards the development of mollic or cambic horizons, which excluded these soils from Fluvisols group according to the statements of WRB classification, Fluvisols are still reported from regulated and drained valleys [10][11][12]32,54,55]. This may indicate that many authors still apply the term "Fluvisols" as a synonym of alluvial soils on the Holocene river terraces, irrespective of the actual stage of their pedogenic transformation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Arid and semi-arid soils contain a high level of salinity as a result of the geological conditions and climatic factors, so the intrusion of saline bodies of water into the coastal aquifers leads to salinity aquifer and groundwater sources. 81 Salinity is the most dissatisfaction of water consumer. However, in arid and semi-arid provinces of Iran hardness is an important problematic issue Kalankesh et al 82 .…”
Section: Watermentioning
confidence: 99%